Technological Addictions and Social Connectedness: Predictor Effect of Internet Addiction, Social Media Addiction, Digital Game Addiction and Smartphone Addiction on Social Connectedness - Savci, Mustafa; Aysan, Ferda (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2017)
Objective: This study examined the predictor effects of four technological addictions, including Internet addiction, social media addiction, digital game addiction and smartphone addiction on social connectedness. Method: The study was conducted on 201 adolescents (101 girls, 100 boys) who have been using Internet, playing digital games, and using social media for at least one year, and have at least one social media account and a smartphone. The Young's Internet Addiction Test-Short Form, Social Media Disorder Scale, Digital Game Addiction Scale, Smartphone Addiction Scale-Short Version, Social Connectedness Scale, and Personal Information Form were used as data collection tools. Parametric statistical methods were used to analyze the data, taking into consideration the single and multivariable normality, linearity, and multicolinearity. Results: The analysis showed that Internet addiction, social media addiction, digital game addiction and smartphone addiction significantly predicted 25% of social connectedness. In addition, it has been determined that the strongest effect on social connectedness is from Internet addiction followed by social media addiction, digital game addiction, and smartphone addiction respectively. Conclusion: Four technological addictions including Internet addiction, social media addiction, digital game addiction and smartphone addiction significantly affect social connectedness.
Keywords: Digital game addiction; internet addiction; smartphone addiction; social connectedness; social media addiction